2013
DOI: 10.1186/1471-244x-13-280
|View full text |Cite
|
Sign up to set email alerts
|

Improving psychotropic drug prescription in nursing home patients with dementia: design of a cluster randomized controlled trial

Abstract: BackgroundNeuropsychiatric symptoms are highly prevalent in nursing home patients with dementia. Despite modest effectiveness and considerable side effects, psychotropic drugs are frequently prescribed for these neuropsychiatric symptoms. This raises questions whether psychotropic drugs are appropriately prescribed. The aim of the PROPER (PRescription Optimization of Psychotropic drugs in Elderly nuRsing home patients with dementia) II study is to investigate the efficacy of an intervention for improving the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 45 publications
(44 reference statements)
1
25
0
Order By: Relevance
“…Moreover, the Hawthorne effect may well have been operating such that prescribers, aware that they were being monitored for this trial, merely changed their behavior because, and while, they were being observed not because of the QUM-D per se . If the tool relied on some interactive component, as we demonstrated with use by nursing staff, this would be consistent with hypotheses that successful de-prescribing is reliant on an interactive and multi-disciplinary process, currently being tested in the recent de-prescribing studies (Smeets et al , 2013 ; Brodaty et al , 2014 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, the Hawthorne effect may well have been operating such that prescribers, aware that they were being monitored for this trial, merely changed their behavior because, and while, they were being observed not because of the QUM-D per se . If the tool relied on some interactive component, as we demonstrated with use by nursing staff, this would be consistent with hypotheses that successful de-prescribing is reliant on an interactive and multi-disciplinary process, currently being tested in the recent de-prescribing studies (Smeets et al , 2013 ; Brodaty et al , 2014 ).…”
Section: Discussionsupporting
confidence: 81%
“…For example, in the Netherlands, the PROPER II study (PRescription Optimization of Psychotropic drugs in Elderly nuRsing home patients with dementia) is being conducted by pharmacists, physicians, and nurses and has three components: preparation and education, conduct, and evaluation/guidance. Primary outcome measures include percentages of patients with appropriate psychotropic drug use and secondary outcomes include overall frequency of psychotropic drug use, neuropsychiatric symptoms, quality of life, activities of daily living, side effects, and mortality (Smeets et al , 2013 ). In Australia, the HALT (halting antipsychotic use in long term care) (Brodaty et al , 2014 ) and the RedUSe studies ( ) are using similar methodologies of multidisciplinary support teams of nurses, psychiatrists, general practitioners, and pharmacists to reduce the inappropriate use of antipsychotic medication in residential care facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Psychotropic drugs and cholinesterase inhibitors are often used to help cognitive function and alleviate NPS in older adults. 35,36 Second, the NPI-Q may be biased by caregiver burden. 37,38 The newer Neuropsychiatric Inventory-Clinician rating scale (NPI-C) may provide a more objective evaluation of NPS.…”
Section: Discussionmentioning
confidence: 99%
“…Although it might be relevant to distinguish between barriers and facilitators related to the intervention and those related to the implementation strategy, the reviewed articles rarely present their results in this manner. Furthermore, several interventions incorporate elements, such as training (Smeets et al, 2013), that are considered implementation strategies by others (Gerritsen et al, 2011). Further research could explore the added value of this distinction.…”
Section: Strengths and Limitationsmentioning
confidence: 99%